Urban Development of Merkinė Town in the 16th–18th Centuries - Buržinskas, Žygimantas (Archaeologia Lituana, 2021)
This study presents data reflecting the urban development of Merkinė in the 16th–18th centuries. The old names of the city streets and the development of the street structure are analyzed. After the analysis of historical sources, the approximate location of the lost masonry and other town buildings is presented, as well as the data of residential and public town buildings and the manor house. In the 16th–18th centuries, wooden buildings dominated in the town, but sources testify that, especially before the mid-17th century war, brick residential buildings were also built in the main town streets. Along with the town hall, the parish church dominated in the structure of the town, as well as the churches and monasteries of the Jesuit residence and the Dominican convent, and on the top of the town a wooden St. Peter’s and St. Paul’s Church stood, which was to be prominently seen in the town’s skyline.
Keywords: Merkinė; Magdeburg city; Grand Duchy of Lithuania; urban structure; royal manor; monastery; residence; Jesuits; Dominicans; 16th–18th century residential buildings